4x + 2y = 7

4x = 7 - 2y

x = (7 - 2y) / 4

y = 5x

(substitute the last equation)

y = 5((7 - 2y) / 4)

y = (35 - 10y) / 4

y = (35/4) - (5y/2)

y + (5y / 2) = 35 / 4

7y / 2 = 35 / 4

7y = 70/4

7y = 35/2

y = 35/14

y = 5/2

4x + 2y = 7

4x + 2(5/2) = 7

4x + 10/2 = 7

4x = 2

x = 1/2

4x = 7 - 2y

x = (7 - 2y) / 4

y = 5x

(substitute the last equation)

y = 5((7 - 2y) / 4)

y = (35 - 10y) / 4

y = (35/4) - (5y/2)

y + (5y / 2) = 35 / 4

7y / 2 = 35 / 4

7y = 70/4

7y = 35/2

y = 35/14

y = 5/2

4x + 2y = 7

4x + 2(5/2) = 7

4x + 10/2 = 7

4x = 2

x = 1/2